Pendidikan Dasar IPAS Pengaruh Model Pembelajaran Think Pair Share (TPS) Terhadap Hasil Belajar IPAS Pada Siswa Kelas IV: Pengaruh Model Pembelajaran Think Pair Share (TPS) Terhadap Hasil Belajar IPAS Pada Siswa Kelas IV - Aji Nugraheni Nugraheni; Ari Suryawan (PendIPA Journal of Science Education, 2023)
This research aimed to determine how the improvement of learning outcomes of fourth-grade students in the subject of Science (IPAS) can be achieved throught the Think Pair Share (TPS) learning model at MI Muhammadiyah Al-Muttaqien. This type of research was quantitative with a Pre-Experimental One Group Pretest-Posttest Design. Data collection techniques included 1) observation and 2) multiple-choice test instruments. The test instruments were administered twice, with a pre-test given before the treatment and a post-test given after the treatment. The statistical test used to test the hypothesis was the paired sample t-test with the assistance of SPSS version 20. The research found that the Think Pair Share (TPS) learning model has an impact on the learning outcomes of fourth-grade students in the subject of science (IPAS), specifically on the topic of plants as a source of life on Earth. This is supported by the average pre-test score of 61,67, which is less than the post-test score of 78,2. The paired sample t-test resulted in a significance value (2-tailed) of 0.000, which is less than 0.05. Therefore, it can be concluded on the IPAS learning outcomes of fourth-grader students at MIM Al-Muttaqien in Sleman Regency.